Mobility of the Singly-Charged Lanthanide and Actinide Cations: Trends and Perspectives - Visentin, Giorgio; Laatiaoui, Mustapha; Viehland, Larry A.; Buchachenko, Alexei A. (Frontiers in Chemistry, 2020)
The current status of the gaseous transport studies of the singly-charged lanthanide and actinide ions is reviewed in light of potential applications to superheavy ions. Previous measurements and calculations for the mobility of lanthanide ions in He and Ar agree well, and they are remarkably sensitive to the electronic configuration of the ion, namely, whether the outer electronic shells are 6s, 5d6s or 6s2. The previous theoretical work is extended here to ions of the actinide family with zero electron orbital momentum: Ac+ (7s2, 1S), Am+ (5f7 7s 9So), Cm+ (5f7 7s2 8So), No+ (5f14 7s 2S) and Lr+ (5f14 7s2 1S). The calculations reveal large systematic differences in the mobilities of the 7s and 7s2 groups of ions and other similarities with their lanthanide analogs. The correlation of ion-neutral interaction potential and mobility variations with spatial parameters of the electron distributions in the bare ions is explored through the ionic radii concept. While the qualitative trends found for interaction potentials and mobilities render them appealing for superheavy ion research, lack of experimental data and limitations of the scalar relativistic ab initio approaches in use make further efforts necessary to bring the transport measurements into the inventory of techniques operating in "one atom at a time" mode.